Strategi Komunikasi Pemasaran Daclen dalam Membangun Positioning di Akun Instagram @daclen.id - Dian Heryani; Detya Wiryany; Ridma Meltareza (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Advances in digital technology have brought significant changes in the way local brands build their brand image and positioning in the market. Social media is one of the main platforms used in marketing communication strategies because of its ability to reach a wide and interactive audience. This research aims to analyze the marketing communication strategy implemented by Daclen, a local fashion brand from Bandung, in shaping sales positioning through the Instagram account @Daclen.id and its official website. The research method used was qualitative descriptive with data collection through in-depth interviews, observations, and documentation. The analysis was carried out using the Circular Method of SOME (Share, Optimize, Manage, Engage) approach which emphasizes the connection between content sharing, message optimization, communication channel management, and active engagement with consumers. The results show that Daclen has succeeded in developing a simple, yet consistent and targeted digital communication strategy. Instagram is used as the primary medium to strengthen the visual power of brands, through uploading high-quality product photos, promotional videos, and active interaction with audiences. Meanwhile, Daclen's official website functions as a credibility center that provides complete information about products, prices, and after-sales service. The combination of the two creates a well-rounded consumer experience and supports an exclusive perception of the brand. Each stage in the SOME model is executed optimally. The Share stage includes the distribution of creative content with a consistent upload schedule. Optimize is done by adjusting messages according to trends and audience responses. Manage focuses on account management and interaction monitoring, while Engage focuses on building emotional connections through quick responses and interactive content. The implications of this study show that the SOME-model-based digital communication approach can help local brands such as Daclen strengthen their positioning, build an exclusive image, and create long-term relationships with consumers amid increasingly fierce competition in the digital fashion industry.